Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1083/jcb.201802155
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella SipA mimics a cognate SNARE for host Syntaxin8 to promote fusion with early endosomes

Abstract: SipA is a major effector of Salmonella, which causes gastroenteritis and enteric fever. Caspase-3 cleaves SipA into two domains: the C-terminal domain regulates actin polymerization, whereas the function of the N terminus is unknown. We show that the cleaved SipA N terminus binds and recruits host Syntaxin8 (Syn8) to Salmonella-containing vacuoles (SCVs). The SipA N terminus contains a SNARE motif with a conserved arginine residue like mammalian R-SNAREs. SipAR204Q and SipA1–435R204Q do not bind Syn8, demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 75 publications
0
31
0
1
Order By: Relevance
“…It displaces host actin‐binding proteins from F‐actin and prevents actin severing, thus contributing to the actin cytoskeleton rearrangements that are required for Salmonella invasion (Zhou et al , ; McGhie et al , ; Higashide et al , ; Lilic et al , ; McGhie et al , ; Lhocine et al , ). Other activities that have been attributed to SipA include Caspase‐3 cleavage and activation (Cain et al , ; McIntosh et al , ), induction of CXC chemokine expression through phosphorylation of IL‐8‐transcription regulatory proteins, JUN and p38MAK (Figueiredo et al , ) and promoting fusion with early endosomes (Singh et al , ). Of relevance to this study, several groups have shown that SipA is also involved in intracellular replication, with the consensus being that it promotes vacuolar replication (Brawn et al , ; Klein et al , ; Singh et al , ; Zhang et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It displaces host actin‐binding proteins from F‐actin and prevents actin severing, thus contributing to the actin cytoskeleton rearrangements that are required for Salmonella invasion (Zhou et al , ; McGhie et al , ; Higashide et al , ; Lilic et al , ; McGhie et al , ; Lhocine et al , ). Other activities that have been attributed to SipA include Caspase‐3 cleavage and activation (Cain et al , ; McIntosh et al , ), induction of CXC chemokine expression through phosphorylation of IL‐8‐transcription regulatory proteins, JUN and p38MAK (Figueiredo et al , ) and promoting fusion with early endosomes (Singh et al , ). Of relevance to this study, several groups have shown that SipA is also involved in intracellular replication, with the consensus being that it promotes vacuolar replication (Brawn et al , ; Klein et al , ; Singh et al , ; Zhang et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Other activities that have been attributed to SipA include Caspase-3 cleavage and activation (Cain et al, 2008;McIntosh et al, 2017), induction of CXC chemokine expression through phosphorylation of IL-8-transcription regulatory proteins, JUN and p38MAK (Figueiredo et al, 2009) and promoting fusion with early endosomes (Singh et al, 2018). Of relevance to this study, several groups have shown that SipA is also involved in intracellular replication, with the consensus being that it promotes vacuolar replication (Brawn et al, 2007;Klein et al, 2017;Singh et al, 2018;Zhang et al, 2018). Here, we found that SipA has no effect on replication per se.…”
Section: Discussionmentioning
confidence: 99%
“…VAMP7 is the v-SNARE in the SNARE complex for heterotypic LE/lysosome fusions with the t-SNAREs STX7, STX8, and VTI1B [70, 71] being replaced by VAMP8 in homotypic LE fusions [72, 73]. In fact, the presence of VTI1B and STX8 on early SCV [69, 74] and their role in STM replication [54], as well as the involvement of VAMP8 in STM invasion were already shown [75]. However, their interaction with SIF remains unclear, except VAMP8 silencing causing SIF reduction identified here (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, this might happen via SPI2-T3SS effector PipB2 that was identified in the recent BioID screen as interactor of VAMP2 [104]. Furthermore, in homotypic EE fusion STX16 is replaced by STX13 [122], and STX13 was previously shown to be present on early SCV [74, 123]. While the exact role of RAB3A and the identity of SNAREs involved remain to be determined, this might indicate that the interception of secretory vesicles depends on a SNARE complex comprising a distinct combination of the abovementioned SNAREs as represented in Figure 8ii.…”
Section: Discussionmentioning
confidence: 99%
“…138 Caspase-3 can degrade SipA to C-terminal and N-terminal: the C-terminal is responsible for actin polymerization and the N-terminal contains an SNARE motif. 139 The latter is responsible for the attachment and recurrence of host syntaxin 8 to SCV. SNARE is involved in endocytosis and syntaxin in rapid endocytosis and vesicle mobilization.…”
Section: Toxinsmentioning
confidence: 99%